Patronazgo en la corte virreinal novohispana: los criados, allegados y paniaguados del marqués de Guadalcázar (1612-1621) - Ayala Tafoya, Eduardo (2021)
Building on the study of political culture in 16th- and 17th-century Imperial Spain, and using unpublished documentation from the Archivo General de Indias, this article aims to analyze the modalities, features, and limits of the Marquis of Guadalcázar’s patronage practices under his administration of New Spain (1612-1621). This insight into the viceroy’s patronage networks identifies the members of his entourage, the role some of them played in pursing their patron’s interests, and their careers in the Indies. Moreover, the viceroy’s largesse encompassed colonial-born “beneméritos”, on whom he also bestowed his favors.